2015
DOI: 10.1080/17518253.2015.1027287
|View full text |Cite
|
Sign up to set email alerts
|

A simple and highly efficient solvent- and catalyst-free synthesis of novelN-sulfamoyl imines

Abstract: The reaction of aldehydes with primary sulfonamides under solvent-and catalyst-free conditions is described. This method affords the N-sulfamoyl imines in short reaction times and high yields. Mild conditions, simplicity, inexpensive and easily available reagents, and absence of any auxiliary substances are some other advantages of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Over the years, the Knoevenagel condensation has taken numerous forms (41)(42)(43)(44). Among the reagents, a wide variety of alkaline compounds were explored, leading to the desired condensation products.…”
Section: Different Amines Introduce Different Knoevenagel Reactionsmentioning
confidence: 99%
“…Over the years, the Knoevenagel condensation has taken numerous forms (41)(42)(43)(44). Among the reagents, a wide variety of alkaline compounds were explored, leading to the desired condensation products.…”
Section: Different Amines Introduce Different Knoevenagel Reactionsmentioning
confidence: 99%
“…Schiff bases have been playing vital roles in e.g. pharmaceuticals, as a protective group, and in liquid crystals (20)(21)(22)(23). In combination with various metals but never alone, it has further been shown that hydrobenzamide exhibits catalytic activity in the field of interactions with biogenic macromolecules such as DNA, RNA, and peptides (24).…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state melt reactions, in which a mixture of solid reactants is melted at eutectic temperature, are noted as one of the green methods and have been successfully used in the synthesis of biologically active molecules. [37][38][39][40][41][42][43][44][45] The remarkable advantages of the solid-state melt reactions, when compared to solution reactions, are (1) higher reaction rate, leading to high product yields in short reaction times since collisions of the reactants are more frequent; (2) high purity of the products with high selectivity, thus no tedious workup and extensive purification required; and (3) no solvents used in the reaction, resulting in reduced costs and amount of chemical waste, thus economic and environmentally friendly. [40,[46][47][48] Notably, there are two reports describing the solid-state melt synthesis of Nacylhydrazones without the need of solvents or catalysts.…”
Section: Introductionmentioning
confidence: 99%